Observasi Faktor Pendorong Produksi Padi: Studi Kasus Kecamatan Tambakdahan Kabupaten Subang - Ratna Komala Putri; Ayu Fahira (Universitas Pasundan, 2022)
This study intends to examine the factors that influence production in the research object area in Tambakdahan District, Subang Regency. In this study, we tested and analyzed the data through the primary descriptive quantitative analysis method where the required data collection data came from rice farmers in Tambakdahan District, Subang Regency. This study focuses on the independent variables, namely land area, number of workers, number of seeds per kilogram, amount of fertilizer per kilogram, and technical irrigation (irrigation) and the dependent variable is the yield of rice production in Tambakdahan District, Subang Regency. The results showed that the variables of land area, fertilizer, and technical irrigation (irrigation) had a partially significant effect, while the labor and seed variables had no significant effect on rice production. But on the other hand, the relationship between variables of land area, seeds, and labor has a negative relationship, while the variables of fertilizer and irrigation technically (irrigation) have a positive relationship.